Molecular Survey of Selected Viruses in Pudus (Pudu Puda) in Chile Revealing First Identification of Caprine Herpesvirus—2 (Cphv-2) in South American Ungulates - Vergara-Egert, P; Moreira-Arce, D (Taylor and Francis Ltd., 2023)
Viral diseases jeopardize the health of wildlife in Chile. However, this country lacks health surveillance programs that allow for defining preventive measures to tackle such diseases. The objective of this study was to determine the occurrence and the genetic diversity of pestivirus, herpesvirus and adenovirus in pudus from Chile. Blood samples from wild (n=34) and captive (n=32) pudus were collected between 2011 and 2019 and analyzed through consensus PCR. All the samples were negative to pestivirus and adenovirus. Herpesvirus was confirmed in four captive, and one wild pudu. All four zoo animals share the same sequence for both polymerase and glycoprotein genes. Both sequences share a 100% identity with caprine herpesvirus-2, classifying them in the same cluster as the Macavirus group. In turn, novel sequences of the polymerase and glycoprotein B genes were obtained from the wild pudu. Our study reports the first evidence of CpHV-2 infection in Chile and South American ungulate populations. Further research will be necessary to assess the pathogenicity of CpHV-2 in this species. It is also urgently recommended that molecular, serological and pathological screening should be conducted in Chilean wild and captive pudus to understand the impact of the herpesvirus on their populations. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.